Ensaio sobre a família pós-moderna - Sanda, Samuel Magoji (2007)
The present dissertation had as objective to study, through an interdisciplinary perspective, the post-modern family, rapporting with two movies My Big Fat Greek Weeding (2002) and About a Boy (2002). The reflection consisted of a brief historical reflection about the function of the family since its ascension in the 19th century until nowadays, time in which it, like the others institutions, is in crisis or disorder. I believe that this crisis that the family is passing through is provoked in part by a narcissistic culture that has been producing young adults that when setting the desire in a central role in their lives are incapables to assume responsibilities preferring virtual relationships to keep at sight more romantic and satisfactory possibilities. Besides, they are incapables to take decisions, because they live in constant oscillation between attraction and repulsion, hope and fear, preferring to appeal to the so-called specialists of human relationships, always ready to offer their services in exchange for fees. As consequence they end up leaving the public space to supposed civics organizations and false politicians. One possible solution that I show to minimize this disorder is a creation of a new political project capable of creating transforming subjects that can, through a new culture, promote the creation of practices that recover the sense of the Illuminist and democratic values